Defect evolution in ZnO and its effect on radiation tolerance. Issue 17 (17th April 2018) - Lv, Jinpeng; Li, Xingji
Abstract : We realized tuning the radiation tolerance of ZnO through engineering the type and concentration of intrinsic defect. Abstract : The origin of ZnO radiation resistance is fascinating but still unclear. Herein, we found that radiation tolerance of ZnO can be tuned by engineering intrinsic defects into the ZnO. The role played by native defects in the radiation tolerance of ZnO was systematically explored by carrying out N + implantation on a set of home-grown ZnO nanocrystals with various lattice defect types and concentrations. Interestingly, decreasing the VO and Zni concentration significantly aggravated N + radiation damage, indicating the presence of O-deficient defects to be the potential cause of the radiation hardness of ZnO. A similar phenomenon was also observed for H + -implanted ZnO. This work offers a new way to manipulate ZnO and endow it with desired physicochemical properties, and is expected to pave the way for its application in radiative environments.